Polyglutamine-containing microglia leads to disturbed differentiation and neurite retraction of neuron-like cells. Issue 9 (September 2020) - Owada, Ryuji; Awata, Saaya; Suzue, Kazutomo; Kanetaka, Hiroyasu; Kakuta, Yohei; Nakamura, Kazuhiro
Abstract: Expanded polyglutamine-containing proteins in neurons intrinsically contributes to neuronal dysfunctions and neuronal cell death in polyglutamine (polyQ) diseases. In addition, an expanded polyQ-containing protein in microglia also leads to apoptosis of neurons. However, detailed morphological analysis of neurons exposed to conditioned medium (CM) derived from polyQ-containing microglia has not been essentially carried out. Here, we introduced aggregated peptide with 69 glutamine repeat (69Q) into BV2 microglial cells. The 69Q-containing BV2 cells showed shorter branches. The CM from 69Q-containing microglia (69Q-CM) induced neurite retraction and fewer number of branch point of neurites of differentiated PC12 cells. Likewise, the 69Q-CM induces disturbed differentiation of PC12 cells with shorter total length of neurites and fewer number of branch point of neurites. Thus, the factor(s) released from polyQ-containing microglia affect both differentiation and degeneration of neuron-like cells. Abstract : Neurite, Polyglutamine, Neuronal death, Molecular neuroscience, Neuroanatomy, Cell culture, Cell differentiation